<span>-6x^4y^5 - 15x^3y^2 + 9x^2y^3
</span>-6x^4y^5 = -2, 3, x, x, x, x, y, y, y, y, y
15x^3y^2 = -5, 3 x, x, x, y, y
9x^2y^3 = 3, 3 x, x, y, y, y
Each group has a 3 in common and each group has 2 x in common and each group has 2 y in common so the GCF = -3x^2y^2
Divide that out and we get
![\frac{-6x^4y^5 - 15x^3y^2 + 9x^2y^3}{-3x^2y^2} =](https://tex.z-dn.net/?f=%5Cfrac%7B-6x%5E4y%5E5%20-%2015x%5E3y%5E2%20%2B%209x%5E2y%5E3%7D%7B-3x%5E2y%5E2%7D%20%3D)
![2x^2y^3 + 5x - 3y](https://tex.z-dn.net/?f=2x%5E2y%5E3%20%2B%205x%20-%203y%20)